Fractal characterization of normal cerebral ventricles in t2-wheigthed magnetic resonance imaging (2017)
Introduction: The fractal geometry describes adequately the irregularity of the natural objects such as the cerebral ventricles, which are irregular structures that can be characterized through the Box-Counting method. Objective: This research aims to develop a new methodology of geometric characterization of the cerebral ventricles, based on the fractal geometry for the analysis of normal cerebral ventricles. Methods: Based on the Box-Counting method, the fractal dimensions of the both lateral ventricles of a normal adult were obtained. Sequential cephalic-caudal 4mm axial slices were acquired on T2-WI, and the differences and similarities of the lateral ventricles were established using the Ventricular Intrinsic Mathematical Harmony. Results: The fractal dimension of the left lateral ventricle had values between 1.0641 and 1,3599, and in the right lateral ventricle had values between 0.8931 and 1.3219. Conclusion: A new morphometric measure of the cerebral ventricles was developed based on the fractal geometry for its use as an objective and reproducible measure.